Roller Coastering Up and Down the Demand Curve of a Durable Goods Monopolist - John John; Dan Bernhardt (Queen's University, Department of Economics, 1995)
This paper considers a durable goods monopolist who can commit to prices at each date, total output, and possibly release dates for stock. The monopolist faces a finite number of arbitrarily patient consumers. Surprisingly, if the monopolist would earn. When the monopolist can also commit to release dates for stock, we show how the optimal pricing rule can be characterized by a programming problem. The monopolist sets high prices in odd periods and low prices in even periods, releasing one good in every odd period. Sufficient conditions are determined for the monopolist's total output to exceed that of a static monopolist.
Keywords: D42; L12; 330; durable goods monoply